Fabrication and Characterization of Glucosamine Hydrochloride from Chitin of Horseshoe Crab Shell (Tachypleus gigas) - Nasution, Aurora Khairani; Agusnar, Harry; Alfian, Zul (Journal of Chemical Natural Resources, 2021)
Preparation of glucosamine hydrochloride from the chitin of horseshoe crab shells using the chemical hydrolysis method has been done using HCl concentration variation ratios of 7%, 9%, 11%,14 % with a ratio of 9:1 (v/w) for 4 hours at a temperature of 90ÂºC. Determination of glucosamine hydrochloride characteristics was characterized using Fourier transform-infra red (FT-IR) spectroscopy, in which the characteristics of glucosamine hydrochloride obtained in the OH group of glucosamine hydrochloride were 3446 cm-1 (s), 3448 cm-1 (s), 3450 cm-1 (s), 3448 cm-1 (s), respectively. For NH group of glucosamine hydrochloride were 1557 cm-1 (s), 1559 cm-1 (s), 1556 cm-1 (s), 1560 cm-1 (s), respectively. For CN group of glucosamine hydrochloride were 1379 cm-1 (m), 1379 cm-1 (m), 1379 cm-1 (m), 1379 cm-1 (m), respectively. While the glycoside bond of glucosamine hydrochloride 1073 cm-1 (w), 1074 cm-1 (w), 1074 cm-1 (w), 1074 cm-1 (w), respectively. Determination of the concentration of glucosamine hydrochloride with Ultraviolet Spectrophotometer analysis at a maximum wavelength of 197 nm with a standard solution of N-acetyl glucosamine in a solution of phosphate acid 0.005%, in which obtained the concentration of glucosamine hydrochloride 7% = 33.67 ppm, 9% = 36.35 ppm, 11% = 40.16 ppm, 14% = 43.97 ppm.